Biology 1 workbook - Ng, Muhammad Ng Chee Hong; Mohd Nasohah, Nor Sa'adah; Abdullah, Azyril Iskandar; Hamzah, Haliza; Teruk, Kamaril Azlah; Mohd Shaharuddin, Norfazlina; Abdul Aziz, Nurul Azrina; Zahari, Shafiyyah Solehah; Abdullah Sani, Siti Hajar; Muslim, Rozita; Ghazali, Zahala (IIUM Press, 2021)
This Biology I Workbook for Biology I course is specially written for foundation students taking Biology I at Centre for Foundation Studies, IIUM. The purpose of this workbook is to provide students with exercises to help them understand topics in Biology I. This Biology I Workbook consists of multiple-choice questions and structure questions for 13 chapters. Answer schemes and feedbacks are provided at the end of each chapter as guidance for the students to understand the concepts. The questions in each chapter were tested on students and moderated to confirm the validity.